Application of caspofungin in China compared with amphotericin B and fluconazole - Zhang CY; Cheng JY; Jiang Y; Liu JY (Dove Medical Press, 2014)
Chunyu Zhang,1 Jiaoying Cheng,2 Yan Jiang,3 Junyang Liu41Department of Health Reform and Development, China–Japan Friendship Hospital, Beijing, People’s Republic of China; 2Department of Obstetrics and Gynecology, China–Japan Friendship Hospital, Beijing, People’s Republic of China; 3National Management Center of 12320 Health Hotline, Chinese Center for Disease Control and Prevention, Beijing, People’s Republic of China; 4Department of Pharmacy, China–Japan Friendship Hospital, Beijing, People’s Republic of ChinaAbstract: Fungal infection has increased in the past 2 decades in China. There are three classes of antifungal drugs, polyenes, azoles, and echinocandins, that are applied frequently in China. Caspofungin, which disrupts the fungal cell wall glucan formation through inhibiting the enzyme 1,3-ß-glucan synthase, is one of the echinocandins. According to the results of clinical practices applied in China, caspofungin has shown to be superior to the other two classes of antifungal drugs, due to its efficacy in treating fungal infection (15% superior to fluconazole); fewer adverse events such as infusion-related reaction, hepatic dysfunction, and vomiting (25%–50% lower incidence rate); rapid resolution of symptoms (about 3 days quicker than amphotericin B); and absence of antagonism in combination with other antifungal drugs. However, caspofungin will remain as a second-line antifungal drug in the near future because of its high price and the policy of health insurance reimbursement in China.Keywords: fungal infection, caspofungin, efficacy, adverse event